2011
DOI: 10.1002/nau.21118
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum nerve growth factor levels in patients with overactive bladder syndrome refractory to antimuscarinic therapy

Abstract: Increased serum and urinary NGF levels in patients with OAB refractory to antimuscarinic treatment suggest these bladder disorders might be caused by chronic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 29 publications
(46 reference statements)
3
34
1
2
Order By: Relevance
“…Responders to antimuscarinic therapy exhibit significantly improved urinary symptom scores and a corresponding decrease in urinary NGF levels, but the reduced NGF levels remained significantly higher than controls [21]. These authors stated that the complex pathophysiology of OAB may be multimodal and could involve several neurotransmitter and inflammatory pathways [21,25]. Our results were not compatible with the literature and changes before and after therapy in OAB-V8 and ICIQ-SF questionnaires were not correlated with NGF/Cr and fractalkine/Cr levels.…”
Section: Pol Scientificcontrasting
confidence: 91%
See 1 more Smart Citation
“…Responders to antimuscarinic therapy exhibit significantly improved urinary symptom scores and a corresponding decrease in urinary NGF levels, but the reduced NGF levels remained significantly higher than controls [21]. These authors stated that the complex pathophysiology of OAB may be multimodal and could involve several neurotransmitter and inflammatory pathways [21,25]. Our results were not compatible with the literature and changes before and after therapy in OAB-V8 and ICIQ-SF questionnaires were not correlated with NGF/Cr and fractalkine/Cr levels.…”
Section: Pol Scientificcontrasting
confidence: 91%
“…Therefore, increased urinary NGF levels in women refractory to antimuscarinic treatment may be related to chronic inflammation [25]. Bladder biopsies have demonstrated histological evidence of inflammatory changes in OAB in the absence of urinary tract infection [5].…”
Section: Pol Scientificmentioning
confidence: 99%
“…Liu et al [24] first reported that serum NGF is also increased in some OAB patients, and according to that study, serum NGF levels were higher in patients with OAB refractory to antimuscarinic therapy. Similarly, our study evaluated the relationship between MetS and NGF levels in OAB patients, and we found that serum NGF levels were elevated in patients with both MetS and OAB compared to the levels in the controls.…”
Section: Discussionmentioning
confidence: 96%
“…Liu et al [40] noted that the serum concentrations of CRP, NGF, IL-1β, IL-6, IL-8, and TNF-α in OAB-dry and OAB-wet study participants were significantly higher than among the controls.…”
Section: Brain-derived Nerve Growth Factormentioning
confidence: 99%